A Historical Analysis of Public Squares in Middle Eastern Cities - Creed D. Hunter & Owen G. Wiggins (International Journal of Innovative and Applied Finance, 2024)
Public squares have long served as centers of social, political, and cultural life. This study examines the historical evolution of urban squares in the Middle East, analyzing their role in shaping community identities and facilitating public discourse. Combining archival research with spatial analysis, the paper highlights the tensions between traditional and modern uses of urban spaces in the context of globalization and urban development